2019
DOI: 10.1002/jor.24402
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Term Pathology of Ovine Lumbar Spine Degeneration Following Injury Via Percutaneous Minimally Invasive Partial Nucleotomy

Abstract: The focus of this work is to assess the long‐term progression of degeneration in the ovine lumbar spine following a minimally invasive model injury comparable to the damage of an intervertebral disc (IVD) herniation. A partial nucleotomy was performed on 18 sheep via the percutaneous dorsolateral approach. The animals were culled at 6 and 12 months to evaluate the damaged and neighboring functional spine units (FSUs) for degenerative characteristics via μ‐CT and histology. Both quantitative μ‐CT and histology … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 41 publications
1
9
0
Order By: Relevance
“…Several degenerative features were detected, such as concave curvature of the lamellae, a blurred AF‐NP boundary, condensation and concave scarring of the matrix, as well as cluster formation of chondrocytes. The histological degeneration values of degenerated and native IVDs according to Hoogendoorn scoring barely changed when comparing the samples harvested 12 months post‐op to those from a similar previous study harvested at 6 months post‐op (Schwan et al., 2019). The degeneration of the native IVDs is possibly attributable to the fact that each test animal harbored damaged, untreated discs as well as damaged, chitosan‐treated discs adjacent to the native discs.…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations
“…Several degenerative features were detected, such as concave curvature of the lamellae, a blurred AF‐NP boundary, condensation and concave scarring of the matrix, as well as cluster formation of chondrocytes. The histological degeneration values of degenerated and native IVDs according to Hoogendoorn scoring barely changed when comparing the samples harvested 12 months post‐op to those from a similar previous study harvested at 6 months post‐op (Schwan et al., 2019). The degeneration of the native IVDs is possibly attributable to the fact that each test animal harbored damaged, untreated discs as well as damaged, chitosan‐treated discs adjacent to the native discs.…”
Section: Discussionmentioning
confidence: 79%
“…Based on previous results, it's been demonstrated that within 6 weeks after surgery pressure‐resisant scar tissue has formed on the damaged side of the IVD, but the original tissue structure cannot be regenerated. Puncture of the IVD via a Sprotte® 21G × 120 mm cannula for injection does not lead to an effect in large animal models as shown in (Schwan et al., 2018, 2019). It is generally accepted that in cadaver experiments the stiffness of the IVD is compromised.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…The animal model used [29] can effectively depict traumatic situations and is suitable for conducting long-term studies of up to one year. For the examination of cell-loaded scaffolds, however, the model described in this study was modified so that discography using an X-ray contrast medium was not necessary.…”
Section: Discussionmentioning
confidence: 99%